The Use of Benzodiazepines in the Management of Hypertensive Crisis: A Literature Review - Stojak, Łukasz; Grego, Mateusz; Baczewski, Mateusz; Popiela, Dariusz; Urbańska, Karina; Grego, Katarzyna; Kwiatkowski, Filip; Czyż, Witold (Quality in Sport, 2025)
Hypertensive crisis is a medical emergency that requires urgent pharmacological intervention to prevent organ damage. The pathogenesis of this condition is often linked to excessive sympathetic nervous system activation resulting from a strong stress response. Benzodiazepines, as a class of drugs with anxiolytic and sedative effects mediated through GABA-A receptor modulation, can effectively target the underlying cause of a sudden rise in blood pressure while indirectly contributing to its reduction. This study presents a literature review on the use of benzodiazepines in the treatment of hypertensive crises, with a focus on their mechanisms of action and the limitations associated with their use. The analysis indicates that benzodiazepines, in specific patient groups, can effectively reduce psychological stress and facilitate hemodynamic stabilization. However, the potential risk of adverse effects, such as respiratory depression, must be considered. Benzodiazepines should be used with caution as a therapeutic option in hypertensive crisis management.